Pregnancy and Prenatal Harm to Offspring: The Case of Mothers with PKU - Robertson, John A. (The Hastings Center report, 1987)
Ethical and legal traditions recognize prenatal duties to avoid harm to offspring. However, applying the harm principle to pregnancy requires a careful balancing of a baby's welfare with a pregnant woman's interest in liberty and bodily integrity. In the case of maternal PKU the mother can prevent harm to her baby by returning to the admittedly unpleasant diet that prevented her from being retarded. Informing, counseling, and access to medical care should be the primary policy. Seizures and forced treatment cannot be justified in this case, and only rarely in other situations.